Distributed Databases for Computer Applications: Study and Selection of Distributed Ledger Technologies - Kleber da Silva Rodrigues, Carlo (iSys - Journal of Information Systems, 2024)
Computer applications on distributed databases are always present in the digital society. An important issue is that these databases be secure, auditable, transparent, and scalable. This article has two objectives: (i) to provide a theoretical baseline on Distributed Ledger Technologies (DLTs) for implementing distributed databases, and (ii) to propose a method for selecting the type of DLT platform for a target organization, called Método Ágil de Seleção (MAS). To this end, we initially investigate literature works and, subsequently, we derive the MAS. Furthermore, we demonstrate the applicability of MAS through a case study. Finally, general conclusions and future works close this article.